Dendrobium naungmungense (Orchidaceae, Dendrobieae), a new species from Kachin State, Myanmar - Liu, Qiang (PhytoKeys, 2018)
Abstract. Dendrobium naungmungense, a new species from Naungmung, Kachin State, North Myanmar, is described and illustrated. It is morphologically similar to D. ciliatilabellum and D. vexabile, but the epichile is oblong with three long-ciliate laminae and the column wing has significant denticulation. A preliminary risk-of-extinction assessment shows that the new species should be regarded as Critically Endangered (CR) according to the IUCN Red List Categories and Criteria.